Organizational capacity and policy integration: government communications strategy in managing COVID-19 in Indonesia - Karlina, Nina; Miftah, Ahmad Zaini; Widianingsih, Ida; Gill, Sarjit Singh (Cogent OA, 2025)
The Covid-19 pandemic is a multifaceted issue for governments globally, and through public communication, social restrictions, and inclusive policies, the community has to obey and follow all the health guidelines to minimize the spread of the virus. This study aims to understand how policy integration, communication, and cognitive dissonance have played out during the pandemic. This study applies causal mechanism tests and cross tabulation in IBM SPSS analysis to assess the impact of strategic communication on 100 ethnic groups in Indonesia by comparing the Covid-19 guidelines with the violation number. Research evidence shows that, despite the presence of well-coordinated policies and communication activities, these could not completely stop policy infringements. Economic factors, cultural norms, and social relations play a critical role in shaping people’s conduct, highlighting the importance of a more refined understanding. Non-governmental organizations, religious leaders, and other groups should also be incorporated to enhance health education and fill the gaps created by government policies. This means that cultural and socioeconomic factors should be taken into account when implementing policies. Thus, health policies are sensitive to the socioeconomic status of the community, in addition to involving leaders for improved control of pandemics.